Re-Evaluating a strategic model for tourism destinations: practical implementation of theories and concepts using a multiple case study approach - Koscak, Marko; O’Rourke, Tony (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2017)
In this work we seek to identify what we see as a dysfunctional barrier in the development of environmentally and economically sustainable tourism at a local level. Changing shifts in tourism markets have led to the greater importance of sustainable tourism initiatives, which by their very nature will tend to have a locally oriented concept, as opposed to a national or international concept. The methodology used has been to apply the four case studies in such a way as to build evidence of the existence of critical success factors. In this way we seek to develop a general model for strategic evaluation. The case studies are examples of sustainable, heritage tourism operating outside major tourism destinations. We elaborate the view that top-down models tend to suffer from weakened impact, unfocused resourcing and diffusion of organizational energy at the point of delivery, due to the bureaucratic elements present in such models. Equally, bottom-up models tend to suffer from a lack of professionalism and expertise on the local level, where there is insufficient human capacity to address and resource the critical success factors and resolve them in strategic and sustainable manner.